Prognostic and diagnostic value of procalcitonin in the post-transplant setting after liver transplantation - Perrakis, Aristotelis; Stirkat, Falk; Croner, Roland S.; Vassos, Nikolaos; Raptis, Dimitrios; Yedibela, Süleyman; Hohenberger, Werner; Mueller, Volker (Archives of Medical Science, 2016)
The aim of the study was to assess the diagnostic accuracy of procalcitonin (PCT) as a marker for complications and as a prognostic factor for mortality after liver transplantation.Liver transplant patients between January 2007 and April 2011 were prospectively included in the study. Procalcitonin serum concentration was recorded before, 6 h after reperfusion and then daily. Postoperative clinical course was prospectively analyzed from admission to discharge. Main surgical data such as operating procedure, type of reperfusion, operating and ischemic times, high urgency (HU) status and MELD score at the time of transplantation were also recorded.Sixteen patients with initial PCT > 5 ng/ml suffered >= 1 complication (p = 0.03). However, there was no association between the level of the 1(st) peak PCT and the further postoperative course or the occurrence of complications. Patients in whom a 2(nd) PCT peak occurred had a significantly higher risk for a complicated course, for a complicated sepsis course and for mortality (p < 0.0001). Warm ischemic time over 58 min, operating time over 389 min and HU status were significant independent factors for a complicated postoperative course (p < 0.001, p < 0.001 and p = 0.03 respectively).Based on our results, we believe that PCT course and the occurrence of a 2(nd) peak seem to possess important diagnostic and prognostic power in the post-transplant setting after liver transplantation.
EVALuna2:15234